Dampak Pengembangan Buku Cerita Bergambar Untuk Anak Usia Dini - Dellya Halim; Ashiong Parhehean Munthe (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2019)
Development in the world of education is very necessary. Innovation and creativity are needed to update and develop existing products or those that want to be developed according to changing times. Picture books that emphasize character values in accordance with the vision and mission of one Kindergarten located in Central Jakarta are very urgent to develop because, at the school , there is no character education book with the value of servite et amate. This was revealed by the teacher through an interview. Based on observations, it was also found that there was indeed no character education book that was in accordance with the school's vision and mission. Picture storybooks are interrelated books between images and text which are the unity of a story. This study uses the research and development method, with the ADDIE model. The data collection techniques used were instrument validation sheets and feedback tests for children. Through the 4 stages of evaluation from experts, the results of the final validation from design experts, linguists and content experts/material get a value of 100% with a very feasible category. From the results of the trials conducted on 2 different classes of treatment, it was shown that this story book illustrated with Layanilah and Cintailah has benefits for kindergarten children. This is evidenced by the mean obtained from the class without the product, namely four questions that get the highest mean value. The other three questions get a low mean. The illustrated storybooks has a positive impact on the understanding of this school, especially in terms of knowing examples of actions that are consistent with the values of servite et amate.